PREVALENCE OF DIABETIC RETINOPATHY IN PATIENT TYPE 2 DIABETES MELLITUS AT INTERNAL MEDICINE POLICLINIC SANGLAH HOSPITAL - Anggia Sari, Ni Made Sintia; Saraswati, Made Ratna (E-Jurnal Medika Udayana; vol 2 no6(2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE One of the complications that can occur in microvaskular diabetes mellitus is diabetic retinopathy. This research was carried out to know the prevalence of diabetic retinopathy in patients type 2 diabetes mellitus at internal divison of Sanglah Hospital. The method used is cross sectional by collecting data from the questionnaire and secondary data of medical record patient's type 2 DM. On this research acquired 111 patients (35.1%) with diabetic retinopathy and (64,9%) nonretinopathy. In the group with good level of HbA1c (<6.5%) the prevalence of diabetic retinopathy obtained 53.2%, in the group of patients with moderate level of HbA1c (6.5-8%) as much as 22.5%, and in the group of patients with HbA1c bad level (>8%) as much as 24.3%. The prevalence of the occurrence of DM complications in the diabetic retinopathy is still high, and a good level of HbA1c does not guarantee a person can’t have complication because the complication can also happens are affected by hypertension, dyslipidemia, age, and duration of DM. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Type 2 Diabetes Mellitus, HbA1c, Retinopathy